The European Social Model in Crisis Is Europe Losing Its Soul? - Vaughan-Whitehead, Daniel (Edward Elgar Publishing, 2015)
The European Social Model has been an integral part of the construction of the European Community and has been effective in stimulating its economic growth. This social dimension represents the soul of the European Union, and has been envied and adopted by other regions and countries in the world. Under the pressure of the 2008 financial crisis and the subsequent introduction of austerity measures across Europe, many countries have reformed basic elements of the model including social protection, pensions, public services, workers' rights, quality of jobs, working conditions and social dialogue, often undermining social cohesion. These trends have raised questions: is Europe currently losing its legacy? If so, what are the social and economic implications, both in the short and longer term? The European Social Model in Crisis assesses social policy developments in each EU individual member state on the basis of detailed empirical evidence and concrete case studies. The volume is a timely warning about the weakening of the European Social Model and its possibly devastating future effects. The alternative options proposed here make the book essential reading for policy-makers, while scholars and researchers of European studies and social policy will find it an invaluable reference.